Magnetoterapia y su efecto en tratamiento de osteocondrosis en deportistas de alto rendimiento de 13 a 20 años; de Federíos, Cantón Babahoyo, Provincia Los Ríos, octubre 2019 – marzo 2020. - Trujillo Contreras, José Vicente (2020)
In the present investigation, we glimpse from a work in explanatory work where you can find very important text in which they express the constant injuries that high-performance athletes of the sports federation of the rivers have, which influences their performance so that they can to develop and their sports activities. This research project was elaborated with a deep bibliographical investigation in which they are framed on the subject of magnetotherapy and its effect in the treatment of osteochondrosis in high performance athletes from 13 to 20 years of Federíos. What can be said that through the instruments that were applied most of the athletes who presented you with pain in different joints could be verified by examinations the doctor diagnosed osteochondrosis. For the development of this research, two groups could be carried out in which one was applied magnetotherapy with a very high frequency and the other with a low frequency but with the combination of an anti-inflammatory, we obtained a very favorable result and group A had a faster improvement so high frequency magnetic waves were applied and they were able to obtain a higher sports performance than group B because they had low magnetic waves but with the combination of an anti-inflammatory called Tensiflex which helped improve both groups its sports activities and therefore its high sports performance.